ANALYSIS OF SENTIMENS IN ONLINE DISCUSSION FORUMS AS A TOOL TO IMPROVE SCHOOLER COMPATIBILITY IN DISTANCE LEARNING - Yulian Purnama; Fathoni Mahardika; Cynthia Petra Haumahu (Indonesian Journal of Education (INJOE), 2024)
This research aims to analyze the use of sentimental analysis in online discussion forums in the context of distance learning. This research method is literary research, in which we review publications and previous research in this field. The results of the study show that sentimental analysis can be used effectively in analyzing student responses to distance learning through online discussion forums. In some studies, it has been found that sentiment analysis can help in measuring student involvement, identifying student needs, and evaluating the effectiveness of teaching. The use of sentiment analysis has successfully improved the quality of student interaction and provided educators with a better understanding of student needs. Moreover, sentimental analysis can also help in assessing the efficiency of the teaching methods used, so that educators can take necessary corrective action.